RESEPSI QS. YĀSĪN AYAT 9 SEBAGAI RITUAL PROTEKTIF DALAM LITERATUR KEISLAMAN: KAJIAN LIVING QUR’AN DENGAN ANALISIS SINKRONIK-DIAKRONIK - Ahmad Ramzi Amirudin (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2021)
This article aims to discuss the reception of QS. Yāsīn :9 as a protective ritual in Islamic literature. The social interaction between the Qur'an and its readers gave birth to various kinds of receptions for it, for example reading the QS. Yāsīn[36]:9 as protection to prevent the house from being stolen. Studying the origins of where this phenomenon originates and how it can develop to become a protection ritual is something interesting to study. Therefore, to achieve this goal, synchronic-diachronic analysis and the theory of informative-performative aspects of Sam D. Gill are used by using Islamic literature as a source to track them, so that the process of transmission and transformation can be seen. The literatures are (1) al-Sīrah al-Nabawiyyah Li Ibn Hisyām by Ibn Hisyām (2) Tafsr al-Qur'ān al-'Aẓīm by Ibn Kaṡīr (3) Mawsū'ah Faḍāil Suwar wa yāt al-Qur' ān by Shaykh Muḥammad bin Razzaq. After analyzing it, it was found that: First, it turns out that this phenomenon originates from the experience of the Prophet Muhammad when he wanted to be killed by the Quraysh infidels based on narrations. Second, synchronously-diachronically, this phenomenon occurs in the transmission process, a transformation process occurs. Third, the transformation process that occurs in this phenomenon can be seen by the different receptions by each author of the book from time to time, namely Ibn Hisyām and Ibn Kaṡīr doing informative receptions, while Shaykh Muḥammad bin Razzaq doing performative receptions.